Magnetic field assisted preconcentration of biomolecules for lateral flow assaying - Sharma, Antareep (2020)
Lateral flow assays (LFA) have been extensively explored for rapid and cost effective point-of-care diagnostics. Typically, LFA responses are influenced by the complexity of sample matrices containing analogues or molecules that may potentially yield non-specific responses, for instance, when assaying for biomarkers in blood, serum and plasma. Therefore, isolation of analytes of interest from sample matrices would significantly improve the LFA responses. Herein, we report a magnetic field assisted preconcentration approach for extraction and assay of proteins in an LFA format. Cardiac marker, Troponin (cTnICT complex), is utilized as a model system for validation of the proposed approach. Magnetic fields of different strengths are evaluated for retaining cTnICT on an LFA membrane utilizing magnetic beads conjugated with anti-Troponin I (anti-TnI) antibodies. The sample matrix components subsequently flows through to the absorbent pad via a hydrophilic passivation layer that is protecting the capturing anti-Troponin C (anti-TnC) antibodies in the test zone. Isolated TnI-magnetic bead complexes are then released to flow downstream along the LFA strip to the test zone upon removal of magnetic field and the passivation layer. The capture of cTnICT magnetic bead complexes at the test zone produces a characteristic brownish band, enabling concentration dependant visual detection of cTnICT. Experimental results indicate that the assay yields pM level sensitivity within 15 min using very low sample volumes (<100 μL), and with possibilities for signal enhancement. The reported assay offers a promising avenue for sensitive detection of target analytes in complex matrices at clinically relevant concentration levels without requiring tedious sample pre-treatment protocols.